Thermal performance of double serpentine minichannel heat sinks: Effects of inlet-outlet arrangements and through-holes. (June 2020) - Cao, Xin; Liu, Huan-ling; Shao, Xiao-dong; Shen, Han; Xie, Gongnan
Highlights: Two novel D-SMPF and D-SMTH are proposed to improve the substrate temperature uniformity. The performance of D-SMTH-A with multi-interleaved inlets and outlets is better than that of the SMPF. Increasing the number of the through-holes can enhance the heat transfer performance. The better substrate temperature can be obtained by using larger diameter through holes. The experimental results agree well with the calculated results in the model of D-SMPF. Abstract: To decrease the substrate temperature gradient of a traditional single serpentine mini-channel heat sink, we present a novel double serpentine heat sink and perform experimental and numerical tests by employee ANSYS FLUENT (version 15) code to trade off the flow and thermal performance of the heat sink. The effects of three inlet-outlet arrangements, the through-hole numbers and the diameter of through-hole on the cooling capacity are compared and analyzed. It can be found that the introduction of interleaved inlet-outlet outperform provides much better uniform substrate temperature, meanwhile, the pressure drop can be reduced by up to 43%, and the average Nusselt number can be raised by up to 26% through punching holes on the channel wall at Qv  = 0.159 L/min. It is also suggested that the double serpentine heat sink using more holes exhibits much better thermal performance attributed to the distinct alleviation of the maximum substrate temperature.